Benchmarking the Performance of Construction Procurement Methods against Selection Criteria in Nigeria - Stephen Okunlola Ojo (Civil Engineering Dimension, 2009)
The study developed performance indices by the widely used procurement options in Nigeria on selection criteria. The traditional mean and standardized ratio were used to form the utility coefficients. Results revealed that performance by the procurement options depended on the respondents’ categorization and cost categorization of projects. Public clients ranked the lump sum contracts more able to achieve speed for projects up to N100 million (Naira) while the private clients believe it is the design-build. As regards quality, public clients rated the Build-Own-Operate-Transfer (BOOT) system as most able to achieve the quality criterion whereas private clients rated design-build for projects up to N100 million (Naira). The study then concluded that, in the Nigerian construction industry participants do not agree on the performance of the procurement options on selection criteria.